Does the brain know who is at the origin of what in an imitative interaction? - Dumas, Guillaume; Martinerie, Jacques; Soussignan, Robert; Nadel, Jacqueline (Frontiers in Human Neuroscience, 2012)
Brain correlates of the sense of agency have recently received increased attention. However, the explorations remain largely restricted to the study of brains in isolation. The prototypical paradigm used so far consists of manipulating visual perception of own action while asking the subject to draw a distinction between self- versus externally caused action. However, the recent definition of agency as a multi-factorial phenomenon combining bottom-up and top-down processes suggests the exploration of more complex situations. Notably there is a need of accounting for the dynamics of agency in a two-body context where we often experience the double faceted question of who is at the origin of what in an ongoing interaction. In a dyadic context of role switching indeed, each partner can feel body ownership, share a sense of agency and altogether alternate an ascription of the primacy of action to self and to other. To explore the brain correlates of these different aspects of agency, we recorded with dual EEG and video set-ups twenty-two subjects interacting via spontaneous versus induced imitation of hand movements. The differences between the two conditions lie in the fact that the roles are either externally attributed (induced condition) or result from a negotiation between subjects (spontaneous condition). Results demonstrate dissociations between self- and other-ascription of action primacy in delta, alpha and beta frequency bands during the condition of induced imitation. By contrast a similar increase in the low gamma frequency band (38-47Hz) was observed over the centro-parietal regions for the two roles in spontaneous imitation. Taken together, the results highlight the different brain correlates of agency at play during live interactions.